Analisis Tindak Tutur Direktif dalam Pamflet Bertema Pendidikan di Lingkungan UMS dan Implementasinya dalam Pembelajaran Bahasa Indonesia di SMP Muhammadiyah 6 Surakarta - Rahmawati, Fitriana Putri; , Prof. Dr. Markhamah, M.Hum (2016)
This study aimed to analyze the type of form directive speech act and speak strategies containedintheenvironmental education pamphlet entitled UMS. The data used in this study is themed pamphlets environmental education in UMS. The data collection technique used is the technique refer to. Data analysis method used is the method followed by the technical frontier frontier frontier referential and pragmatic techniques. The results of this study are as follows. (1) Based on the analysis of the kind of form of speech acts directive found four types of forms of speech acts directive contained in the pamphlet namely, (a) that informs 14 discourse, (b) sent 8 discourse, (c) reminds 7 discourse, (d) call-7 discourse. (2) Pursuant to form strategic analysis tells discovered two forms of personality strategies contained in the pamphlet namely, (a) the strategy speak directly 23 discourse, (b) strategies 8 tells indirect discourse.